PENINGKATAN INTERAKSI SOSIAL ANAK MELALUI PERMAINAN SCRABBLE - Musrifah, Nika; Mardiyati, Siti; Djannah, Wardatul (Consilium: Jurnal Program Studi Bimbingan dan Konseling, 2013)
The purpose  of this  study was  to  determine  the effectiveness  of  the scrabble games to the development of social interactions with the peer group of a elementary school students in Temanggung. This research was pre-experimental design. The subject of the research were 38 elementary school students. Based on the result of hypothesis, it is known that there are development of social  interactions  with  peer group  before and after treatment  by scrabble games that is tcount=4,105 compared with ttable=1,68 or tcount>ttable (p value 0,000<0,05). The result of the research that scrabble games is efective to develop the social interactions with peer group in Elementary School students.